Pertolongan Pertama Anak Kejang Demam - Handayani, Rahmaya Nova (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
Children are unique creatures with different physiological functions. This difference of course also has an impact on the health status of children, such as their susceptibility to fever and seizures, the first aid measures taken will have an impact on the subsequent health status of the child. However, based on some research results for handling first aid in various cases such as fever and seizures, most of them have sufficient knowledge around 50%, good around 15% and 35% are lacking. So, in this case, it is concluded that the handling of first aid in children still needs to be improved. This consultation focuses on the first treatment of children with fever and seizures. Because these 2 cases are the most common that occur in children. The purpose of the activity is to improve the knowledge and skills of handling first aid in children with fever and seizures in all parents at PAUD Sinar Mentari Purwokerto. The activity plan was carried out in the form of coordination of activities with puskesmas, coordination with parents, identification of health problems, joint problem solving in the form of counseling, training and preparation of activity reports. The results before being given counseling the majority of knowledge levels were lacking 66.6%, and after counseling with good knowledge 54.2%. There is an increase in parental knowledge and skills towards the first cut in children with febrile seizures.